STRATEGY IMPROVES THE NUMBER OF NEW STUDENTS IN SEKOLAH MENENGAH ATAS NEGERI 1 GETASAN THROUGH ISHIKAWA DIAGRAM APPROACH (FISHBONE): STRATEGI MENINGKATKAN JUMLAH PESERTA DIDIK BARU DI SEKOLAH MENENGAH ATAS NEGERI 1 GETASAN MELALUI PENDEKATAN DIAGRAM ISHIKAWA (FISHBONE) - Pachlan, Pachlan Pachlan (Jurnal Pencerahan, 2019)
The purpose of this study is to identify the factors that influence the interests of prospective students to register at Sekolah Menengah Atas (SMA) Negeri 1 Getasan. The technique used in this research is to analyze and process the data based on Ishikawa diagram techniques. The results of this study were to determine the strategies that were formulated including: (1) Implementing additional learning and tutoring for students who have prominent academic potential;(2) Developing a local curriculum on entrepreneurship related to food processing subjects such as making geplak waluh; (3) Completing classroom facilities; (4) Optimizing Multimedia and Computer laboratories by organizing their use for Junior High School that do not yet have facilities; (5) Enacting policies that take into account the economic capabilities of surrounding communities for children who attend SMA Negeri 1 Getasan; (6) Implementing policies by considering cross-subsidies especially for students whose parents come from the environment around the school; (7) Establishing better cooperation with the community around the school, especially with regard to certain events; and (8) Scheduling activities targeting junior high school students such as the Festival Band for junior high school or holding an open house on high school anniversaries.